Welfare effects of TTIP in a DSGE model - Philipp Engler; Juha Tervala (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Several studies have analyzed the trade and output effects of the Transatlantic Trade and Investment Partnership (TTIP) between the United States and the European Union, but our paper is the first attempt to study its welfare effects. We measure the welfare effect of TTIP as the percentage of initial consumption that households would be willing to pay for TTIP in order to remain as well off with TTIP as without it. The discounted present value of the welfare gain of TTIP, which leads to the elimination of tariffs and cuts in non-tariff measures by 25%, is in the range of 1% to 4% of initial consumption, depending on the parameterization. The welfare gain increases in the elasticity of substitution between domestic and foreign goods. The bulk of the welfare gain is caused by cuts in non-tariff measures.
Keywords: F13; F41; E60; 330; tariffs; TTIP; trade agreement; trade liberalization